Usefulness of Xpert® Carba-R on enrichment broth for the early detection of carbapenemase-producing Enterobacterales. (November 2021) - Girlich, Delphine; Ouzani, Souad; Langlois, Isabelle; Fortineau, Nicolas; Naas, Thierry; Dortet, Laurent
Highlights: Culture-based screening of CPE using enrichment broth is sensitive but causes delay Molecular-based screening of CPE is rapid but might miss low-level carriage Molecular biology on enriched broth might have both sensitivity and rapidity ABSTRACT: Early detection of patients colonized with carbapenemase-producing Enterobacterales is crucial to limit their spread. Molecular biology tests are rapid but might miss low-level carriage. Culture-based methods using enrichment are cheap and detect low-level carriage but cause delay. Two clinical cases are reported, which demonstrated that molecular biology (Xpert® Carb-R) on enriched broth cumulates advantages of both strategies. In both cases, this strategy enabled early detection of patients colonized at low-level with carbapenemase-producing Enterobacterales because it saved 24 hours in detection time.